An Alternative Explanation for the “Fed Information Effect” - Bauer, Michael D.; Swanson, Eric T. (American Economic Review, 2023)
Regressions of private-sector macroeconomic forecast revisions on monetary policy surprises often produce coefficients with signs opposite to standard macroeconomic models. The “Fed information effect” argues these puzzling results are due to monetary policy surprises revealing Fed private information. We show they are also consistent with a “Fed response to news” channel, where both the Fed and professional forecasters respond to incoming economic news. We present new evidence challenging the Fed information effect and supporting the Fed response to news channel, including: regressions that control for economic news, our own survey of professional forecasters, and financial market responses to FOMC announcements. (JEL D82, E23, E27, E43, E44, E52, E58)